The Standing of Zuhd in al-Ibriz Authored by Sheikh Bisri Mustafa | مقام الزهد في تفسير الإبريز للشيخ بشري مصطفى - Azkiyatut Tahiyah (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2017)
In society, zuhud oftenly became one of the misunderstood religious topic among people. Many of those who had just learned it decided to abandon the glamor of the whole world and declare that he is a zuhud. This study aims to determine the pattern and method of one of the archipelago mufassir K.H. Bisri Mustafa in his work al-Ibriz, focusing on the interpretation of the related verses of the zuhud. In this study, the author tries to examine the verses regarding the discussion of Sufism, especially standing of (maqom) zuhud. The whole interpretation of the verse explains that the afterlife is better than the life of the world which is only deceit and temporary. Kyai Bisyri also invites people not to get lost in the life of the world and apply zuhud in it.